Penerapan model pembelajaran cooperative script untuk meningkatkan keterampilan menyimak peserta didik sekolah dasar - Anugrahaning Della Puspitasari; Retno Winarni; Supianto Supianto (Universitas Sebelas Maret, 2024)
This research uses a cooperative script learning model to improve the listening skills of class III B students at SDN Mangkubumen Kidul for the 2023/2024 academic year, totaling 26 people. This research used Classroom Action Research (PTK) which was carried out over two cycles and two meetings in each cycle. Teachers and students are the data sources for this research and the techniques for obtaining the data are through tests, interviews, observation and documentation. This research uses validity tests in the form of source triangulation and technique triangulation. Data were analyzed using the methods in the Miles and Huberman model, namely data collection, data reduction, data presentation and drawing up conclusions. The findings of this research show that there was a significant increase in the results of cycle I with an average value of 70.5 and an increase in cycle II to 83. The conclusion of this research is that the listening skills of class III students at SDN Mangkubumen Kidul can be improved through the application of the cooperative script learning model.